State Responsibility in Fulfilling The Constitutional Right to Social Security: Evaluation of Actuarial Accountability and Financing - Yuli Farianti; Ahmad Redi (Journal Customary Law, 2026)
Discourse concerning state responsibility in fulfilling the constitutional right to social security is often constrained by the dilemma between normative mandates and fiscal capacity realities. Article 28H paragraph (3) and Article 34 paragraph (2) of the 1945 Constitution imperatively position the state as the principal axis in administering a universal national social security system. The sustainability of such a system heavily depends on the precision of actuarial accountability as an instrument for long-term risk projection. Failure to accurately project technical risks and the establishment of financing structures that are inconsistent with benefit obligations create serious threats to the resilience of the social security system. A juridical-doctrinal approach reveals a significant gap between the state’s obligation as the ultimate guarantor and the current management practices of trust funds, which remain largely reactive in nature. Decisions of the Constitutional Court further affirm the state’s position in guaranteeing absolute certainty of social protection for all citizens. Evaluation of financial governance demonstrates that neglecting actuarial valuation in strategic policymaking directly contributes to systemic instability. Dependence on ad hoc state budget interventions indicates the weakness of the current national financing system’s independence. Actuarial accountability must therefore be positioned as a mandatory risk-control instrument integrated into regulatory frameworks in order to prevent the risk of default. Synchronization between fiscal policy and rigorous actuarial calculations constitutes an essential prerequisite for fulfilling citizens’ constitutional rights. These fundamental rights must not be reduced to mere legal promises without adequate financial support. The transformation of the financing system toward a resilient, transparent, and risk-based model constitutes a crucial step in ensuring social justice. An ideal financing structure must be capable of balancing financial independence with the state’s obligation to protect the human dignity of all citizens. The integration of a unified data system and independent actuarial audits will strengthen the state’s credibility in sustainably managing public funds across generations.